Uma abordagem metabolômica em pacientes com Leucemia Linfocítica Crônica e Sìndrome Mielodisplásica - Flávia Favretto (2018)
Chronic Lymphocytic Leukemia (CLL) and Myelodysplastic Syndrome (MDS) are hematological malignancies that result in quantitative and qualitative changes in blood cells. In CLL, neoplastic cells (B lymphocytes) accumulation in lymph nodes, bone marrow and peripheral blood is observed, whereas in MDS a hypercellular bone marrow and peripheral blood pancytopenia are observed. Both hematological malignancies have staging systems limitations favoring the search for clinical and biological markers that can improve these diseases prediction. The metabolomics is a recent analytical approach that seeks the identification and quantification of the metabolites present in the biological samples and other. The variations in plasma concentrations indicated by it may be useful to investigate possible biomarkers. However, the applications of this analysis in patients with leukemias are still incipient.Plasma samples from 22 patients with CLL and 11 MDS patients from the Hematology and Oncology Unit of Hospital das Clínicas of the Federal University of Minas Gerais and of 19 healthy individuals who constituted the control group were analyzed. Metabolites were analyzed using a quantitative and controlled metabolomic target based on Absolute / DQ® p180 Kit (Biocrates Life Sciences AG, Innsbruck, Austria) instructions. The Ultra Performance Liquid Chromatography (UPLC) technique associated with the tandem quadrupole mass analyzer was used. The validated assay allowed a comprehensive identification and quantification of 186 endogenous metabolites, including 21 amino acids, 19 biogenic amines, 40 acylcarnitines, 90 glycerophospholipids, 15 sphingolipids and 1 sum of hexose. The data were based on multivariate statistical methods (SIMCAP + (14.0.1, MKS) and univariate (MATLAB). PCA, PLS-DA and OPLS-DA statistical models were used to create a metabolic ranking (significance from a p <0.05). Metabolic routes were analyzed through HMDB, KEGG and MBROLE databases. Were selected some metabolites that were which were highlighted by an increase or decrease in concentration levels in CLL and SMD when compared to control group, belonging to acylcarnitines, biogenic amines, amino acids and glycerophospholipids chemical class. Metabolic profile preliminary analysis of this experiment allowed identification of metabolites related to cancer metabolism processes, which may be considered possible targets for future research of diagnostic and prognostic markers as well as therapeutic targets.